Metoda deschisă de coordonare (MDC) în domeniul protecției și incluziunii sociale. Dimensiunea participativă a MDC - Lambru, Mihaela (Calitatea Vieții, 2010)
The Open Method of Coordination (OMC) is now considered a new method of governance, promising more effectiveness and coherence in European policy-making. The present article intends to present the main characteristics of OMC policy instrument, its evolution during the last decade and the implications for new Member States as Romania. The OMC as policy instrument has a dual structure: to one side is a policy instrument generating common knowledge production and, to the other side is a policy process aiming to support participation, to encourage the public authorities to open the policy process to various stakeholders in social policy area. This article examines the conditions in which the OMC is implemented in Romania, as a new EU Member State, and the conditions which can make Romania to take advantage of the OMC policy framework.